Learning to like disgust: neuronal correlates of counterconditioning - Schweckendiek, Jan; Klucken, Tim; Merz, Christian J.; Kagerer, Sabine; Walter, Bertram; Vaitl, Dieter; Stark, Rudolf (Frontiers in Human Neuroscience, 2013)
Converging lines of research suggest that exaggerated disgust responses play a crucial role in the development and maintenance of certain anxiety disorders. One strategy that might effectively alter disgust responses is counterconditioning. In this study, we used functional magnetic resonance imaging (fMRI) to examine if the neuronal bases of disgust responses are altered through a counterconditioning procedure. One disgust picture (conditioned stimulus: CS+disg) announced a monetary reward, while a second disgust picture (CS-disg) was never paired with the reward. Two neutral control pictures (CS+con / CS-con) were conditioned in the same manner. Analyses of evaluative conditioning showed that both CS+ were rated significantly more positive after conditioning as compared to the corresponding CS-. Thereby, the CS+disg and the CS+con received an equal increase in valence ratings. Regarding the fMRI data, ANOVA results showed main effects of the conditioning procedure (i.e. CS+ vs. CS-) in the dorsal anterior cingulate cortex. Further, main effects of the picture category (disgust vs. control) were found in the bilateral insula and the orbitofrontal cortex. No interaction effects were detected. In conclusion, the results imply that learning and anticipation of reward was not significantly influenced by the disgust content of the CS pictures. This suggests that the affect induced by the disgust pictures and the affect created by the anticipation of reward may not influence the processing of each other.